Avaliação do processo de elaboração de um plano estratégico: o caso EMLUR João Pessoa PB. - Miranda Neto, João Henrique de (2007)
The main objective of this thesis is to evaluate the strategic planning process carried out in municipal solid waste collection agency (EMLUR) of the city of João Pessoa, Paraíba, Brazil. The research adopted a quantitative-qualitative methodological approach to this case study. The factors that determine organizational performance were examined through a review of the origin and evolution of strategic planning. This theoretical and methodological foundation was applied to the case study and proved to be particularly appropriate. The research revealed that EMLUR s strategic plan was developed through surveys, studies, interviews and especially through workshops conducted in accordance with the PEP methodology (Souto-Maior, 2002). The participants of these workshops were managers of EMLUR, who formed a strategic management group. The PEP process demonstrated that the agency mainly and urgently needed to respond to two strategic issues, i.e, fundamental problems that affect the whole organization. One of the issues was concerned with the external environment and was targeted to its main objective- to keep the city clean. The other was concerned with its internal environment and focused in its human resources. To tackle the two issues the PEP process led the agency to strategic actions and six projects. Thus, in the EMLUR case, the planning approach enabled the agency to reach its main objectives, both in terms of process and results.